ANALISIS KEKERABATAN GENETIK BERBASIS KARAKTER FENOTIPE PADA BEBERAPA GALUR HARAPAN BUNGA MATAHARI (Helianthus annuus L.) - Mukhammad Irwan Kurniadi; Adellia Rahmatika (Universitas Nias Raya, 2026)
The sunflower plant (Helianthus annuus L.) is widely known as a source of vegetable oil with an oil content reaching 40-50%. This research was conducted to analyze the genetic relationships of several promising sunflower lines based on their phenotypic characters. The research was carried out in Srigading Village, Bantul Regency, Special Region of Yogyakarta, from December 2025 to March 2026. The study used a Randomized Block Design (RBD) with 9 promising lines and 3 replications, resulting in 27 experimental units. The observed characters consisted of 11 quantitative and 5 qualitative characters. The data were analyzed using the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) based on Gower’s General Similarity Coefficient, as well as Principal Component Analysis (PCA). The results from the 9 lines using PCA were divided into two Principal Components with a cumulative diversity value of 83.03%, and the cluster analysis showed that the 9 promising lines formed 3 main clusters.